2015
DOI: 10.1007/s12223-015-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial resistance of Salmonella strains from food of animal origin in southern Italy

Abstract: Six hundred fourteen strains of Salmonella enterica were isolated from 16,926 samples of food of animal origin collected in southern Italy from 2003 to 2012. The isolates were identified, serotyped, and challenged against 15 antibiotics according to the protocol defined at national level for veterinary isolates of Salmonella (EnterVet surveillance network). Salmonella serotypes Typhimurium, Hadar, Enteritidis, Derby, and 4,[5],12:i:- were those most frequently isolated. The widest resistances were recorded tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…The rate of Salmonella's resistance to sulfonamide found in this study was 25%, which is different from the rates reported by other investigators; Khallaf et al reported 64% in Morocco [25], and Proroga et al observed 69% in Italy [44]. This could be due by the wide use of this antibiotic for a long time as an antiinfective [45].…”
Section: Discussioncontrasting
confidence: 97%
“…The rate of Salmonella's resistance to sulfonamide found in this study was 25%, which is different from the rates reported by other investigators; Khallaf et al reported 64% in Morocco [25], and Proroga et al observed 69% in Italy [44]. This could be due by the wide use of this antibiotic for a long time as an antiinfective [45].…”
Section: Discussioncontrasting
confidence: 97%
“…This result is in agreement with those obtained by other authors, which found reduced efficacy of this antimicrobial against salmonellae, maybe because of the indiscriminate use in humans and animals therapy [40][41][42].…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to those in a report from Tunisia (20%) 22 but lower than those detected previously in Morocco (75.43%) 23 , Italy (84.2%) 24 and China (74%) 25 . In this study, 14.7% of Salmonella isolates (5/34) were resistant to two types of antibiotics.…”
Section: Discussionsupporting
confidence: 90%